School inclusion of children with intellectual disability: An intervention program. Issue 4 (2nd October 2019) - Nota, Laura; Ginevra, Maria Cristina; Soresi, Salvatore
ABSTRACT: Background: This study evaluated the impact of a structured 10-didactic units intervention on promoting the school inclusion of elementary school students with intellectual disability (ID). Method: The intervention was devised for 152 Italian typically developing (TD) elementary school students that were randomly assigned to the experimental (EG) or to the control (CG) group. Specifically, we examined the positive and negative social behaviours that took place in naturalistic class settings between TD students and their classmates with ID and the positive and negative peer sociometric nominations that children with ID received from their TD classmates. Results: At post-test, the children with ID included in the classes randomly assigned to the EG, received more positive sociometric nominations and social behaviours than peers with ID of the CG, and adopted more positive behaviours towards TD peers. Conclusions: The study highlighted the potential of the intervention to promote the school inclusion of students with ID.